Doing a doctorate in educational ethnography - Walford, Geoffrey (Studies in educational ethnography ;, 2002)
Doing a doctorate in education is always a challenging and difficult process. Doing a doctorate in education that is based upon ethnographic research is even more so. This title draws together a series of semi-autobiographical reflexive accounts of the process of doing a doctorate using educational ethnography. The individual studies include research into school effectiveness, the experiences of Asian teenagers, sexual cultures in the primary school, mature students on Access courses, primary school management, the experiences of children with special educational needs, teachers' work intensification, the family and school experiences of Year 9 students and a Youth Training programme within English professional football. The range of topics shows how import ethnographic work has become in education. Most of the contributors are still at the early stage of their academic careers. Their writings have not yet attained "classic" status - although some may be on the way to such status. The doctoral process is still a vivid memory in their minds and they have been able to drawn upon their fieldnotes and recollections to construct accounts that shed light on their experience and help to demystify it. The book should be of value for those who are thinking of doing a doctorate, for others still struggling through the process and for their supervisors.